Emission of Carbon Dioxide Influenced by Different Water Levels from Soil Incubated Organic Residues - M. B. Hossain; A. B. Puteh (The Scientific World Journal)
We studied the influence of different organic residues and water levels on decomposition rate and carbon sequestration in soil. Organic residues (rice straw, rice root, cow dung, and poultry litter) including control were tested under moistened and flooding systems. An experiment was laid out as a complete randomized design at 25°C for 120 days. Higher CO2-C (265.45 mg) emission was observed in moistened condition than in flooding condition from 7 to 120 days. Among the organic residues, poultry litter produced the highest CO2-C emission. Poultry litter with soil mixture increased 121% cumulative CO2-C compared to control. On average, about 38% of added poultry litter C was mineralized to CO2-C. Maximum CO2-C was found in 7 days after incubation and thereafter CO2-C emission was decreased with the increase of time. Control produced the lowest CO2-C (158.23 mg). Poultry litter produced maximum cumulative CO2-C (349.91 mg). Maximum organic carbon was obtained in cow dung which followed by other organic residues. Organic residues along with flooding condition decreased cumulative CO2-C, k value and increased organic C in soil. Maximum k value was found in poultry litter and control. Incorpored rice straw increased organic carbon and decreased k value (0.003 g d−1) in soil. In conclusion, rice straw and poultry litter were suitable for improving soil carbon.